Nature of association between rural background and practice location: A comparison of general practitioners and specialists - Humphreys John S; McGrail Matthew R; Joyce Catherine M (BMC, 2011)
Abstract Background Rural and remote areas are characterised by a shortage of medical practitioners. Rural background has been shown to be a significant factor associated with medical graduates' intentions and decisions to practise within a rural area, though most studies have only used simple definitions of rural background and not previously looked at specialists. This paper aims to investigate in detail the nature of the association between rural background and practice location of Australian general practitioners (GPs) and specialists Methods Data for 3156 GPs and 2425 specialists were obtained from the Medicine in Australia: Balancing Employment and Life (MABEL) study. Data on the number of childhood years resident in a rural location and population size of their rural childhood location were matched against current practice location. Logistic regression modelling was used to calculate adjusted associations between doctors in rural practice and rural background, sex and age. Results GPs with at least 6 years of their childhood spent in a rural area were significantly more likely than those with 0-5 years in a rural area to be practising in a rural location (OR 2.28, 95% CI 1.69-3.08), whilst only specialists with at least 11 years rural background were significantly more likely to be practising in a rural location (OR 2.27, 95% CI 1.77-2.91). However, for doctors with a rural background, the size of the community that they grew up in was not significantly associated with the size of the community in which they currently practise. Both female GPs and female specialists are similarly much less likely to be practising in a rural location compared with males (GPs: OR 0.53, 95% CI 0.45-0.62). Conclusions This study elucidates the association between rural background and rural practice for both GPs and specialists. It follows that increased take-up of rural practice by new graduates requires an increased selection of students with strong rural backgrounds. However, given the considerable under-representation of rural background students in medical schools and the reluctance of females to practise in rural areas, the selection of rural background students is only part of the solution to increasing the supply of rural doctors.